Performance of Millennial Employees of Four-Star Hotels in Medan City with Harmonious Dedication as an Intervening Variable - Azwar Hasibuan, Hasrul; Syaifuddin, Syaifuddin; Rusiadi, Rusiadi (IJBLE Scientific Publications Community Inc., 2025)
This study examines the performance of millennial employees in four-star hotels in Medan, with harmonious dedication as an intervening variable. The research employs the Partial Least Square – Structural Equation Model (PLS-SEM) for data analysis. The findings indicate that workload does not significantly influence harmonious dedication or employee performance. Conversely, worker autonomy positively impacts both harmonious dedication and employee performance. Work passion significantly affects employee performance but does not contribute to harmonious dedication. Work innovation plays a crucial role, significantly influencing both harmonious dedication and employee performance. Additionally, harmonious dedication enhances employee performance and serves as a mediating variable in the relationship between work innovation and employee performance. However, it does not mediate the effect of work passion on performance. These results highlight the importance of worker autonomy and work innovation in improving employee performance, while workload and work passion have limited direct effects. The study provides insights for hotel management to focus on enhancing autonomy and innovation to boost employee dedication and performance. Future research can explore additional factors influencing millennial employee performance in the hospitality industry.